Direct and Indirect Treatment of Organic Dye (Acid Blue 25) Solutions by Using Cold Atmospheric Plasma Jet - Kumar, Amit; Škoro, Nikola; Gernjak, Wolfgang; Povrenović, Dragan; Puač, Nevena (Frontiers in Physics, 2022)
In this work, the direct and indirect removal of Acid Blue 25 (AB25) from water by using cold atmospheric pressure plasma jet (APPJ) has been demonstrated. APPJ with a pin electrode type configuration operating with argon as a working gas was used as a plasma source for treatments. In this configuration, argon plasma was formed in the contact with surrounding air over the liquid surface. The plasma was driven by using a high voltage radio frequency (RF) power supply. The system was characterized by the measurement of electrical characteristics and by employing optical emission spectroscopy (OES). The electrical characterization gave information about the voltages and currents, i.e. working points of the discharge, as well as power deposition to the sample. OES recorded the emission spectra and confirmed several existing reactive species in the gas phase of the plasma system. During the direct treatment, AB25-containing solution was directly exposed to APPJ. The direct treatment was performed by modifying various experimental parameters, such as initial AB25 concentrations, treatment times, and input powers. In the indirect treatment, AB25 was treated by using plasma activated water (PAW). The characterization of PAW was performed and various plasma-induced long-lived species, such as nitrate (NO3-), nitrite (NO2-) and hydrogen peroxide (H2O2) have been quantified using colorimetric techniques. Besides, blank experiments have been conducted with main constituents in PAW, where AB25 was treated individually by NO3-, NO2- and H2O2 and with a mixture of these three species. As expected, with the direct treatment almost complete removal of AB25 was achieved. The measurements also provided an insight into the kinetics of the degradation of AB25. In the indirect treatment, PAW removed a significant amount of AB25 within 17 days. In the blank experiments, H2O2 containing solutions created a favourable influence on removal of AB25 from liquid.